CULTURE, EDUCATION AND PSYCHOLOGY: BRAZILIAN INDIGENOUS FORMATION AND THE SOCIAL MEDIA CONTEXT - Cialdini, Robert Beno; Antônio da Silva, Renan; Alves, Felipe Freitas de Araújo (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2022)
The social relevance of this research is based not only on the fact that it makes it possible to perceive that new technologies are also mighty present in many indigenous communities, which already tensions colonialists paradigms, but to acknowledge how these technologies are transmitting knowledge to make it possible to broaden discussions about the conceptions of indigenous education and culture, raising reflection on whether it is feasible or not to use Youtube as an educational, technological tool, especially with a focus on an anti-colonialist education. Because Youtube is a place of broad access, used by both teachers and students of primary and higher education, it is interesting to know the existence of specific channels that deal with indigenous education, as well as to critically analyze their contents, before using them as educational tools on indigenous people.